Effect of Arbuscular Mycorrhyzal Fungi in Improving Soybean Growth in Ultisol Soil - Mahmudin; Palupi, Dora; Susianti, Helda; Siahaan, Limartaida; Yanti, Yus Dwi; Barokah, Abi (Research and Social Study Institute, 2025)
Background: Soybean is one of the most popular agricultural commodities in Indonesia, but its production is still low. Thus, it is necessary to make efforts to expand its agriculture in the form of marginal land development.Aims: This study aims to examine the effect and obtain the best treatment dose of arbuscular mycorrhizal fungi (AMF) in ultisol soil to increase the growth of soybean plants (Glycine max (L.) Merill).Methods: This experimental study employed a complete randomized design (CRD) with the treatment of arbuscular mycorrhizal fungi (AMF). The AMF treatment comprised five levels: no AMF, 4 g/polibag, 8 g/polibag, 12 g/polibag and 16 g/polibag. Each treatment was repeated four times, resulting in 20 experimental units and each experimental unit comprised three polybags so that this study used 60 polybags. The data were analyzed using Analysis of Variance (ANOVA) and continued with Duncan's New Multiple Range Test (DNMRT) at the 5% level.Result: AMF treatment is able to increase the growth of soybean plants in the parameters of plant height, number of productive branches, flowering age, number of flowers, and harvest age. The AMF treatment dose of 12 g/polybag is proven to give the best results in increasing the growth of soybean plants. The use of AMF can be an effective strategy in optimizing soybean production, especially on marginal lands.